2010
DOI: 10.1158/0008-5472.can-10-0046
|View full text |Cite|
|
Sign up to set email alerts
|

C-Propeptides of Procollagens Iα1 and II that Differentially Accumulate in Enchondromas versus Chondrosarcomas Regulate Tumor Cell Survival and Migration

Abstract: Chondrogenic tumors that exhibit benign or malignant behaviors synthesize variable amounts of cartilagelike extracellular matrix. To define the regulators of these phenotypes, we performed a proteomic comparison of multiple human chondrogenic tumors, which revealed differential accumulation of the C-propeptides of procollagens Iα1 and II (PC1CP and PC2CP) in malignant versus benign tumors, respectively. Expression patterns of PC1CP correlated with levels of tumor vascularization, whereas expression patterns of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…Indeed, the immobilized form of the COOH-terminal propeptide of procollagen IIa1 was shown to induce apoptosis in primary human chondrocytes and in the EAhy926 human endothelial cell line. 34 Also fragments of collagen XVIII and collagen IVa were shown to suppress tumor growth in vivo and in vitro by inhibiting angiogenesis and inducing apoptosis, respectively. 35,36 In contrast, the propeptide of procollagen I was shown to induce migration and promote vascularization of breast tumor xenograft in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the immobilized form of the COOH-terminal propeptide of procollagen IIa1 was shown to induce apoptosis in primary human chondrocytes and in the EAhy926 human endothelial cell line. 34 Also fragments of collagen XVIII and collagen IVa were shown to suppress tumor growth in vivo and in vitro by inhibiting angiogenesis and inducing apoptosis, respectively. 35,36 In contrast, the propeptide of procollagen I was shown to induce migration and promote vascularization of breast tumor xenograft in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although soluble PC2CP also increased VEGF expression, expression of CXCR4 and of matrix metalloproteinase 13 was more pronounced. This experimental evidence suggested that PC1CP favors angiogenesis and tumor progression, but immobilized PC2CP blocks angiogenesis and reduces tumor progression via apoptosis while soluble PC2CP favors tumor progression and metastasis [14]. These results suggested that detection of these peptides might have potential diagnostic and prognostic use.…”
Section: Introductionmentioning
confidence: 92%
“…Specificity of the antibodies was verified by Western blotting, which showed a single band at expected position of 34 KDa for both PC1CP and PC2CP, and by immunohistochemistry using 28 nontumor and tumor samples [14].The following dilutions were used: PC1CP, 1/200; PC2CP, 1/200. Immunohistochemistry was performed with a Dako Autostainer Plus (Dako, Glostrup, Denmark) with LSAB + system-HRP K0679 revelation system (Dako), using biotin-streptavidin amplification and diaminobenzidine as a chromogen, following the manufacturer's instructions.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the survival of chondrogenic tumors is associated with altered abundance of collagen C-terminal propeptides [21]. Comparative profiling of diseased and normal cartilage from human donors demonstrated a role for the serine protease Htra1 in matrix degradation [22].…”
Section: Post-translational Regulation Of Matrix Properties and The Emementioning
confidence: 99%